2021
DOI: 10.1071/ah20331
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of automated dispensing cabinets and inventory robots for centralised distribution of medication in an Australian hospital

Abstract: ObjectiveIn Australian hospitals, a central distribution system is often utilised to supply medication to clinical areas. This study investigated the impact of automated dispensing cabinets (ADCs) and inventory robots in medication distribution within an Australian hospital. MethodsA prospective observational study of pharmacy technician medication supply to clinical areas was conducted over a 2-week period pre- and post-implementation of ADCs and inventory robots. Information was collected on the time taken t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The PRISMA flowchart of the review is reported in Figure 1. Nine peer-reviewed publications [35][36][37][38][39][40][41][42][43] out of the 261 records retrieved with the initial search, met the eligibility criteria Table 1. The evaluation of the scientific evidence indicated a potentially high risk of bias, and a low-quality literature level was observed for all three outcomes of interest Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PRISMA flowchart of the review is reported in Figure 1. Nine peer-reviewed publications [35][36][37][38][39][40][41][42][43] out of the 261 records retrieved with the initial search, met the eligibility criteria Table 1. The evaluation of the scientific evidence indicated a potentially high risk of bias, and a low-quality literature level was observed for all three outcomes of interest Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies juxtaposed the Central Pharmacy-Based automated scenario with the manual dispensing scenario [35] reported that pharmacy automation could enhance the time allocated for picking and the total turnaround time for discharge (p<0.01). [43] examined the efficiency outcomes before and after implementing a central dispensing drug system, demonstrating a reduction in the overall time for drug dispensing by 15%, attributable to the introduction of automation. Four studies contrasted the Ward-based automated scenario with traditional dispensing.…”
Section: Efficiencymentioning
confidence: 99%
“…Data can also be used to note trends in medication use hospital‐wide and increase or reduce stock levels accordingly 14, 15 . Programmes can be designed to convert inventory levels from robots and ADCs into imprest orders, saving time and paper in comparison to manual ordering 16 …”
Section: Theme 1 — Environmental Sustainabilitymentioning
confidence: 99%
“…14,15 Programmes can be designed to convert inventory levels from robots and ADCs into imprest orders, saving time and paper in comparison to manual ordering. 16 It is possible that the 39% of FPs who positively responded that budgets will be increased for solutions to reduce waste are already utilising the data from their current pharmacy automation (Figure 1, Item 7). Increasing knowledge and accessibility of the data that can be leveraged from technology solutions is paramount in reducing medication wastage.…”
Section: Summary Of Responsesmentioning
confidence: 99%